Enhanced Performance of Electrochemical Sensors Based on Nanosized NiO Particles. (2017) - Carbone, Marilena; Nesticò, Alessia; Bellucci, Noemi; Micheli, Laura; Palleschi, Giuseppe
Abstract: A novel NiO nanoparticles modified screen printed electrode (SPE) was developed that couples the easy-to-use advantages of this technology to the pseudocapacitance properties of NiO. In order to find the conditions for achieving the best performing modified SPEs, NiO nanoparticles were purposely synthesized via a microwave assisted procedure followed by calcination at 400 °C or 600 °C. The two sets of NiO nanoparticles were dispersed in various solvents and at different loads. The structural and electrochemical characterization was carried on by X-ray Diffraction, Scanning Electron Microscopy and Cyclic Voltammetry using ferricyanide as electroactive probe. It was found that, in general, all modified electrodes show better performances compared to the bare electrodes. It must also be noted that the nanoparticles undergo a partial re-aggregation on the electrode surface. The best performing electrode is the one modified with NiO calcined at 400 °C (the NiO400/H2 O), which is also the one most homogenously dispersed on the electrode surface. Probed against several compounds, the NiO400/H2 O modified electrode demonstrates superior electrochemical performances, with respect to literature data in terms of peak intensity enhancement relative to the bare electrodes and resolution of the reduction peaks.